PENGARUH GAYA KEPEMIMPINAN, BUDAYA ORGANISASI, MOTIVASI DAN KOMPETENSI TERHADAP KINERJA PEGAWAI DINAS KOPERASI USAHA KECIL DAN MENENGAH DAN PERDAGANGAN KABUPATEN SUKOHARJO - Sarmiyati; Ahmad Husin; Dian Noor Citra Perdana (JURNAL ILMIAH EDUNOMIKA, 2025)
This research aimed to know the effect of leadership style, organizational culture, motivation and competence on the performance of employees of the cooperative, small and medium enterprises and trade service of sukoharjo regency. The population of this study was 78 employees of the Cooperatives, Small, and Medium Enterprises and Trade Office of Sukoharjo Regency. The sampling technique used in this study was census, meaning that the entire population was included in the sample. The sample size for this study was 78 people. 1) Leadership style significantly influences the performance of employees at the Office of Cooperatives, Small, and Medium Enterprises and Trade in Sukoharjo Regency. the results of this research show that Organizational culture significantly influences the performance of employees at the Office of Cooperatives, Small, and Medium Enterprises and Trade in Sukoharjo Regency. Motivation significantly influences the performance of employees at the Office of Cooperatives, Small, and Medium Enterprises and Trade in Sukoharjo Regency. Competence significantly influences the performance of employees at the Office of Cooperatives, Small, and Medium Enterprises and Trade in Sukoharjo Regency. Leadership style, organizational culture, motivation, and competence simultaneously influence the performance of employees at the Office of Cooperatives, Small, and Medium Enterprises and Trade in Sukoharjo Regency. Of the four variables, the variable that most dominantly influences the performance of employees of the Cooperatives, Small and Medium Enterprises and Trade Service of Sukoharjo Regency is Competence, because the value of b4X4 (0.427) > b3X3 (0.393) > b2X2 (0.374) > b1X1 (0.254). Keywords : the influence of leadership style, organizational culture, motivation, competency, employee performance